Toponym of Ban Kang Pla: Guidelines for Designing and Developing Community Products from Kang Pla Tree Through Participation Process to Promote Grassroot Economy of Ban Kang Pla Community, Mueang District, Loei Province - Phoungmanee, Thairoj; Yamyim, Weeranuch; Luerngam, Piyanuch; Chatphibunphuwiang Hoaherm, Pheeraphat (Journal of International Studies, Prince of Songkla University, 2024)
This academic article aimed to 1) study the toponym and context of Ban Kang Pla and 2) study the guidelines for designing and developing the community products from Kang Pla trees through participation process for promoting the grassroot economy of Ban Kang Pla community, Mueang District, Loei Province. An interview, focus group conversation, meeting, and an evaluation form were used as research tools for evaluating the design and development of the community products. The obtained data was analyzed using content analysis. The results showed that the toponym of Ban Kang Pla was originated from Kang Pla trees growing and covering the area along the Loei River. Then, the villagers named the village after the name of Kang Pla tree to show the identity of the area. Kang Pla is a small shrub normally growing in wet areas. The guidelines for designing and developing the community products from Kang Pla trees through participation process were divided into 7 stages as follows: 1) making inspiration and concepts of products, 2) searching for community’s identity, 3) searching for product information, 4) designing and drafting products, 5) trying using Kang Pla Tree products, 6) criticizing and evaluating products, and 7) marketing and promoting the products